Second peak of plasma diazepam concentration and enterogastric circulation. - Ma Yue-Ming; Sun Rui-Yuan (Acta Pharmacologica Sinica, 2016)
Intragastric food administration caused a pronounced second peak of plasma diazepam concentration in rabbits after iv diazepam 5 mg.kg-1. The second peak disappeared after gastrostomy and choledochostomy. A large amount of diazepam was found in the gastric juice while its content in bile remained at a much lower level during the whole experiment. These results suggested that diazepam may undergo an enterogastric circulation in addition to its enterohepatic circulation, with the former mainly contributing to the appearance of the second peak.